ANTIGEN PROTEIN FROM SCHISTOSOMA MANSONI: NEW PARADIGM OF SYNTHETIC VACCINE DEVELOPMENT - GOMASE V.S; CHITLANGE N.R. (International Journal of Pharma and Bio Sciences, 2010)
Schistosoma mansoni causative agent of schistosomiasis. Peptide fragments of antigen protein can be used to select nonamers for use in rational vaccine design and to increase the understanding of roles of the immune system in parasitic diseases. Analysis shows MHC class II binding peptides of antigen protein from Schistosoma mansoni are important determinant for protection of host form parasitic infection. In this assay, we used PSSM and SVM algorithms for antigen design and predicted the binding affinity of antigen protein having 393 amino acids, which shows 385 nonamers. Binding ability prediction of antigen peptides to major histocompatibility complex (MHC) class I & II molecules is important in vaccine development from Schistosoma mansoni.